2012
DOI: 10.5398/medpet.2012.35.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone and Blood Metabolites Concentrations of Broiler Chickens Subjected to Feeding Time Restriction

Abstract: ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh pembatasan waktu makan terhadap konsentrasi hormon tiroid dan metabolit darah ayam broiler selama periode pembatasan dan pemulihan. Sebanyak 400 ekor ayam broiler unsexed strain Lohmann umur 7 hari ditempatkan pada 5 perlakuan dengan menggunakan rancangan acak lengkap dan dianalisa menggunakan ANOVA. Perlakuan terdiri atas: ransum yang diberikan ad libitum (R-0); ransum yang disediakan 2 jam pada pagi hari dari pukul 08:00-10:00 dan 2 jam pada sore hari da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These results are support to those of Azis et al [23]. Previous studies in poultry have indicated that dietary dilution can improved the plasma levels of hormones.…”
Section: Blood Biochemical Indicatorssupporting
confidence: 92%
“…These results are support to those of Azis et al [23]. Previous studies in poultry have indicated that dietary dilution can improved the plasma levels of hormones.…”
Section: Blood Biochemical Indicatorssupporting
confidence: 92%
“…It is suspected that with an increase in total phenol, antioxidant activity is higher and greater than low phenol levels. Duckweed is often used as a traditional medicine because it has a variety of benefits such as: anticancer, antidiabetic (Korivi et al 2012), antifungal (Vizzotto et al 2015), antimicrobial (Pickler et al 2013;Tian et al 2015), anti-inflammatory and analgesic (Xu et al 2015;Moreno et al 2015;Kusmayadi et al 2018), antioxidant (Mushawwir et al 2010(Mushawwir et al , 2011Hecker and McGarvey 2011;Fabris et al 2017), and sedative activity from the nervous system (Azis et al 2012;De Castro et al 2013;Pouyssegur and Mechta-Grigoriou 2016). These activities can be produced because of the role of chemical compounds contained therein such as alkaloids, phenols, flavonoids (He et al 2009) and the other report showed some chemicals such as tannins, anthocyanins, glycosides, bufadienolides, saponins, coumarin, sitosterol, quinine, and lectins (O'Brien et al 2010;Rhoads et al 2013;Shehab-El-Deen et al 2014).…”
Section: Antioxidants Statusmentioning
confidence: 99%
“…Rajion et al (2001) reported that N/L ratio and serum glucose concentration in goats were significant elevated during transportation at an ambient temperature of 29 o C. In the stressful condition of transport, adrenokortikoid activity is also increased and indicated by an increase in cortisol level. In addition to this hormone, stress condition can also affect the secretion of the thyroid hormone, triiodothyronine (T3) and tetraiodothyronine/thyroxine (T4) with various mechanisms (Hangalapura et al, 2004;Astuti et al, 2010;Azis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%